2001
DOI: 10.1159/000050423
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic Twins Discordant for External Hydrocephalus

Abstract: External hydrocephalus (EH) is a transient, developmental condition in infancy characterized by macrocephaly and prominence of the subarachnoid spaces. The cause is unknown, but many patients have a family history consistent with autosomal dominant inheritance. This report describes a pair of monozygotic twins, only one of whom – the recipient of a twin-twin transfusion – has EH. Whatever the genotype of the twins, their discordant phenotypes suggest that the disproportionate calvarial growth that characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…Proposals include obstruction of the CSF flow at the level of the arachnoid villi [9], delayed frontal lobe development [10] and inappropriate skull versus brain growth [11,12]. In our population, we noted a male predominance, as has been seen in other series.…”
Section: Discussionsupporting
confidence: 66%
“…Proposals include obstruction of the CSF flow at the level of the arachnoid villi [9], delayed frontal lobe development [10] and inappropriate skull versus brain growth [11,12]. In our population, we noted a male predominance, as has been seen in other series.…”
Section: Discussionsupporting
confidence: 66%
“…The dominant inheritance might be due to a single gene exhibiting a major effect as part of a multifactorial phenomenon in some families [166], probably during a limited time of susceptibility in fetal development [134]. Maytal et al suggested that the primary phenotype merely was the delayed maturation of the arachnoid villi [110].…”
Section: Resultsmentioning
confidence: 99%
“…Some have even suggested that the skull is growing faster than the brain for some time, giving a transient subarachnoid CSF accumulation [124, 134]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors hypothesized that the underlying cause is a cephalocranial disproportion [ 31 ]. Lastly, subarachnomegaly has also been contemplated to be caused by a developmental disturbance of inadequate skull growth in relation to brain growth [ 32 ]. The most commonly cited immature arachnoid villi theory hypothesizes that a failure in CSF absorption would lead to dilation of cortical subarachnoid spaces because of a reabsorption deficit from the subarachnoid spaces.…”
Section: Pathophysiologymentioning
confidence: 99%